Implementation of Universal Primary Education Programme in Uganda and its Influence on Education Performance - Mutabaruka, Fredrick; Kazooba, Charles Tushabomwe (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2017)
This study was an assessment of implementation process of Universal Primary education (UPE) programme in Uganda and how it influences the performance of the programme. The principal whim for undertaking this study was the yearning to assess the quality of UPE in Uganda derived from the view that having reached the year 2015, the year that was set for achieving UPE Millennium Development Goal number 2, and the national commitment to improving quality primary education remains unclear. In order to attain this, a combination of research methods have been conducted particularly the interviews and documentary analysis; where 11interviews were carried out. Further analysis was done on content documents Annual Education Abstracts from the Ministry of education and sports and some reports from NAPE and UWEZO. From the findings, quality implementation framework was not followed, implementation process influences programme performance, and it’s not only implementation that influences performance but also other factors.
Keywords: Universal Primary Education; Education reforms; Free Education; Decentralisation; School Faculties Grant